Small Signal Stability Enhancement of a Wind Energy Integrated Power System by UPFC Optimal Damping Controller - Nahak, Narayan; Kumar Mallick, Ranjan; Kumar Pandey, Rajan; Mumtazun Nabi, Md.; Panigrahi, Dibyasha; Samal, Arup (International Journal of Engineering and Technology, 2018)
This work presents a dual optimal PI controller based on UPFC for the purpose of enhancing stability of small signals of a power system integrated with wind energy source. The parameters of controller are tuned by PSO-GWO algorithm. System responses have been obtained with varying wind penetration to power system and for different operating conditions detail eigen value analysis is performed. The results predict that, variable wind power penetration deteriorates dynamic stability of power system and proposed UPFC controller can damp system oscillations much effectively ac compared to PSO and GWO optimized single PI controllerÂ Â